2009
DOI: 10.1002/smll.200801220
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics, Copper Release, and Toxicity of Nano‐ and Micrometer‐Sized Copper and Copper(II) Oxide Particles: A Cross‐Disciplinary Study

Abstract: An interdisciplinary and multianalytical research effort is undertaken to assess the toxic aspects of thoroughly characterized nano- and micrometer-sized particles of oxidized metallic copper and copper(II) oxide in contact with cultivated lung cells, as well as copper release in relevant media. All particles, except micrometer-sized Cu, release more copper in serum-containing cell medium (supplemented Dulbecco's minimal essential medium) compared to identical exposures in phosphate-buffered saline. Sonication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
269
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(296 citation statements)
references
References 40 publications
22
269
4
1
Order By: Relevance
“…Here, we have demonstrated that synthesized nano-CuO has a higher solubility than commercial nano-CuO (2.5% versus 0.74%, Table 1), probably due to differences in size and purity. The size of synthesized nano-CuO is $10 nm while commercial nanoCuO is between 30 and 100 nm (Table 1 and Figure S1), and it has been demonstrated that small nanoparticles have higher dissolution rates than large particles (Midander et al, 2009). On the other hand, the presence of impurities in the commercial nanoCuO may lower its dissolution rate in a similar way as iron doping decreases the solubility of zinc oxide nanoparticles (nano-ZnO) and leads to a lower toxicity than non-doped nano-ZnO Xia et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Here, we have demonstrated that synthesized nano-CuO has a higher solubility than commercial nano-CuO (2.5% versus 0.74%, Table 1), probably due to differences in size and purity. The size of synthesized nano-CuO is $10 nm while commercial nanoCuO is between 30 and 100 nm (Table 1 and Figure S1), and it has been demonstrated that small nanoparticles have higher dissolution rates than large particles (Midander et al, 2009). On the other hand, the presence of impurities in the commercial nanoCuO may lower its dissolution rate in a similar way as iron doping decreases the solubility of zinc oxide nanoparticles (nano-ZnO) and leads to a lower toxicity than non-doped nano-ZnO Xia et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…CuNPs target the cell membrane causing a rapid loss of its integrity, which then leads to cell death. Conversely, CuONPs appear endocytosed within cells in the first hours of interaction which is followed by DNA damage [11].…”
Section: -Introductionmentioning
confidence: 99%
“…These findings are in contrast to studies of other nano-sized particles where increased toxicity has been associated with a decrease in size. 5,9,12,34,35 Generally, the higher surface area is cited as the likely cause of increasing toxicity. A major difference between many of the nanoparticles previously studied and the fluoromicas is their aspect ratio.…”
Section: Discussionmentioning
confidence: 99%